Optimization of the ITO frontal electrodes for flexible CdTe thin film solar cells - Khrypunov, G.S. (Functional Materials, 2006)
The optimization of the ITO frontal electrodes for flexible solar сells on CdTe base was carried out by annealing in air at 430℃. It has been shown, that for "superstrate" ITO/CdS/CdTe/Cu/Au solar cells, the preliminary annealing of ITO films provides the efficiency increase from 8.5 % up to 11.3 %, while for NaCl/ITO/CdS/CdTe/Cu/Au "substrate" solar cells, from 2.2 % up to 7.8 %. Шляхом вiдпалу на повiтрi при температурi 430℃ виконано оптимiзацiю фронтального електроду ITO для гнучких плiвкових сонячних елементiв на основi телуриду кадмiю. Показано, що для сонячних елементiв ITO/CdS/CdTe/Cu/Au (типу "superstrate") попереднiй вiдпал шарiв ITO забезпечує зростання ефективностi вiд 8.5 % до 11.3 %, для сонячних елементiв NaCl/ITO/CdS/CdTe/Cu/Au (типу "substrate") вiд 2.2 % до 7.8 %. Путем отжига на воздухе при температуре 430℃ проведена оптимизация фронтальных электродов ITO для гибких солнечных элементов на основе теллурида кадмия. Показано, что для солнечных элементов ITO/CdS/CdTe/Cu/Au (типа "superstrate") предварительный отжиг слоев ITO обеспечивает рост эффективности от 8,5 % до 11,3 %, а для солнечных элементов NaCl/ITO/CdS/CdTe/Cu/Au (типа "substrate") от 2,2 % до 7,8 %.